Incidental vs. symptomatic diagnosis of follicular lymphoma: implications of earlier detection - Suheil Albert Atallah-Yunes; Matthew J. Rees; Raphael Mwangi; Robyn L. Kuchler; Ahmed Alnughmush; Grzegorz S. Nowakowski; Thomas M. Habermann; Yucai Wang; Jose C. Villasboas Bisneto; Andrew L. Feldman; Matthew J. Maurer; James R. Cerhan; et al. (Blood Cancer Journal)
Abstract Follicular lymphoma (FL) is usually diagnosed at an advanced stage when the patient presents with a palpable lymph node or symptoms such as pain and fatigue. However, due to advances in imaging techniques used for many diseases and cancer screening, incidental diagnosis of FL is expected to rise. In this study, we investigated FL disease characteristics and outcomes in patients diagnosed incidentally versus symptomatically, providing insights into what might be detected with multi-cancer early detection tests (MCEDs). We conducted a review of 908 patients with newly diagnosed FL enrolled in the Mayo Clinic component of the Molecular Epidemiology Resource (MER) from 2002 to 2015. We compared disease characteristics and outcomes between the incidental and symptomatic groups. Of the 908 patients, 259 (28.5%) were diagnosed incidentally. The incidental group was more likely to present with early-stage disease (stage I/II: 43.2% vs. 30.6%, p = 0.0003), normal lactate dehydrogenase (LDH) levels (87.2% vs. 80.8%, p = 0.03), and trended towards having lower FLIPI scores (49.8% vs. 42.2%, p = 0.1). However, there were no significant differences in event-free survival (EFS), overall survival (OS) or lymphoma-specific survival (LSS) between the two groups. In conclusion, incidental detection of FL is associated with earlier stages and more favorable disease characteristics. However, this did not translate into improved survival outcomes. Whether even earlier detection of FL using emerging MCEDs translates into improved outcomes remains an open question requiring further investigation.